GPR sounding of aufeis and alluvium of aufeis glades in the Kyubyume River valley, Oymyakon Highlands - D. E. Edemsky; V. E. Tumskoy; I. V. Prokopovich (Лëд и снег)
Aufeis is a surface accumulation of ice which is formed as layer-by-layer freezing of underground or river water periodically pouring onto the surface in winter. In July 2022, a geophysical survey was carried outin the valley of the Kyubyume River. The study was performed for the purpose to check a possibility to use GPR (150 and 250 MHz) for investigating internal structure of ice bodies, locations of underchannel taliks, and inferred zones of groundwater discharges, as well as revealing ice bodies in the gravel-pebble alluvium of the aufeis glade. The thickness of the aufeis amounted to 2.2 m, the geological cross-section was sounded down to depths of 4.5–8 m. Profiles were studied at right angles to the main channel of the river, including with access to the shoal of the glade. The measurement results did show that the layered ice of the aufeis is not a homogeneous medium for the GPR method, so this method may be used to study structure of the ice,and to investigate the processes of the aufeis formation. Two layers with a thickness of 1.1 m and 0.9 m were isolated in the aufeis ice, with ε = 4.1 and ε = 3.4, respectively. In the underlying alluvium, a cross bedding of the channel deposits was found that was the result of the river watercourse migration. In the sand and pebble deposits underlying the aufeis, a sub-horizontal layer was identified at depths of 2.5–3 m, which is presumably a lens of high-icy sedimentary rocks or underground ice.